Transformational Leadership: Application Of Self-Transcendence By School Principals - Firdaus, Hanif; Farikha, Lany (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Transformational educational leaders can be said to apply self-transcendence because they tend to have a broader vision, prioritize collective needs, and are committed to sustainable change. They see education as a tool to shape a better society. This study employs field research, interviews, and a literature review using a descriptive qualitative approach, which is a research process that generates descriptive data in the form of written or spoken expressions obtained directly from the field. The data is then analyzed using the triangulation method to produce valid and comprehensive results. The results of this study are: 1) Transformative leadership is a combination of leadership abilities and transformation skills. It involves the ways a leader influences the behavior of their subordinates to work together and productively to achieve organizational goals, as well as changing their basic attitudes and values through empowerment. 2) The principal has an important role in motivating teachers and students, but the principal must also continuously motivate themselves for quality and productivity improvement. 3) Transcendent leaders are able to inspire and motivate teachers and students through their actions and words, fostering a spirit for learning and development.